2020
DOI: 10.37708/ezs.swu.v18i1.18
|View full text |Cite
|
Sign up to set email alerts
|

F O R E I G N L a N G U a G E T E a C H I N G M E T H O D O L O G Y

Abstract: The capability to use cultural cues in order to function effectively in culturally diverse situations has been measured by the fashionable concept of cultural intelligence (CQ) and its four dimensions (metacognitive CQ, cognitive CQ, motivational CQ and behavioral CQ) in a lot of previous studies and research. This capability is an important asset of the competitive portfolio for almost all companies in today's globalized world. Our study builds on a recent intensive research and brings anew the issue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 11 publications
(18 reference statements)
0
15
0
5
Order By: Relevance
“…CBT is seen as the "gold standard" intervention for many psychological problems in young people with average intellectual functioning. Meta-analyses and systematic reviews support the use of CBT and CBT elements for youth with a wide range of disorders both in the internalizing as well as externalizing spectrum (e.g., Riise et al, 2020;Wergeland et al, 2020). Similar studies have shown specific ingredients to be effective for specific types of disorders (e.g., Garland et al, 2008;Hogue et al, 2020;Okamura et al, 2020).…”
Section: Cognitive Behavior Therapy: a Potentially Effective Treatmen...mentioning
confidence: 87%
“…CBT is seen as the "gold standard" intervention for many psychological problems in young people with average intellectual functioning. Meta-analyses and systematic reviews support the use of CBT and CBT elements for youth with a wide range of disorders both in the internalizing as well as externalizing spectrum (e.g., Riise et al, 2020;Wergeland et al, 2020). Similar studies have shown specific ingredients to be effective for specific types of disorders (e.g., Garland et al, 2008;Hogue et al, 2020;Okamura et al, 2020).…”
Section: Cognitive Behavior Therapy: a Potentially Effective Treatmen...mentioning
confidence: 87%
“…Maybe if we assume another form of F , we will obtain another new black hole which will be different from the black hole given by Equation () and (). Moreover, there could be any analytic spherically symmetric interior solution can be derived from the field Equation () following the procedure done in [113].…”
Section: Discussionmentioning
confidence: 99%
“…The data on which this article is based are available open access from Mendeley Data (Murray et al., 2023).…”
Section: Data Availability Statementmentioning
confidence: 99%